PENYEDIAAN BAHAN AJAR INOVATIF HIDROKARBON BERBASIS PROBLEM BASED-LEARNING TERINTEGRASI KEARIFAN LOKAL MINYAK KARO: penelitian pendidikan kimia - Silaban, Ramlan; lespiani, ika; Daulay, Rabiah; Ginting, Elfrida; Sitorus, Marham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem raised in this study is related to the way of teaching and learning in the classroom which is still teacher-oriented and the learning resources used have not connected the material with everyday life situations. This study aims to design a hydrocarbon learning module that links the local wisdom of Karo oil using the Problem Based Learning (PBL) approach. The method applied is Research and Development (R&D) with the 4D development model (Define, Design, Development, Disseminate). Evaluation of the module's feasibility was carried out by media experts, material experts, and chemistry teachers, and also through student responses. The results of the study showed that the module met the requirements for use in SMA Negeri 2 Kabanjahe, with a high average validation percentage. Student responses showed that this module was effective in increasing their interest and motivation in studying hydrocarbon material.